Evolution of a species-specific determinant within human CRM1 that regulates the post-transcriptional phases of HIV-1 replication. - Nathan M Sherer; Chad M Swanson; Stéphane Hué; Roland G Roberts; Julien R C Bergeron; Michael H Malim (PLoS Pathogens)
The human immunodeficiency virus type-1 (HIV-1) Rev protein regulates the nuclear export of intron-containing viral RNAs by recruiting the CRM1 nuclear export receptor. Here, we employed a combination of functional and phylogenetic analyses to identify and characterize a species-specific determinant within human CRM1 (hCRM1) that largely overcomes established defects in murine cells to the post-transcriptional stages of the HIV-1 life cycle. hCRM1 expression in murine cells promotes the cytoplasmic accumulation of intron-containing viral RNAs, resulting in a substantial stimulation of the net production of infectious HIV-1 particles. These stimulatory effects require a novel surface-exposed element within HEAT repeats 9A and 10A, discrete from the binding cleft previously shown to engage Rev's leucine-rich nuclear export signal. Moreover, we show that this element is a unique feature of higher primate CRM1 proteins, and discuss how this sequence has evolved from a non-functional, ancestral sequence.